The Effect of Mentoring and Emotional Freedom Technique (M-EFT) on Nurses Students' Readiness and Anxiety Facing Competency Tests - Efroliza, Efroliza (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2023)
Introduction: Competency Test is one of the mandatory instruments by the government to ensure quality graduates. Guiding students to prepare optimal results in the competency test, one of which is mentoring. The purpose of this study was to determine the effect of mentoring and emotional freedom technique (M-EFT) on the readiness and anxiety of nurse students to face the competency test. Method: This study is a quantitative study with a quasi-experimental research design with a pre-test and post-test approach with a control group with a statistical test used, namely the Mann Whitney test. The population in this study were nursing students from two institutions, namely the Muhammadiyah Palembang Institute of Health and Technology and the Musi Charitas Catholic University Palembang with a total sample of 153 people. Results:There is a significant effect (0.001) of the intervention of mentoring and emotional freedom technique (M-EFT) on the readiness and anxiety of co-ners students to face the competency test. Conclusions: there is a significant effect of M-EFT on students' readiness and anxiety to face the competency test. It is hoped that the M-EFT intervention can be used as an alternative method in overcoming the problem of learning readiness and anxiety in co-ners in educational institutions.